Survival without neurological impairment of a patient with rhino-orbito-cerebral zygomycosis - Timóteo, Carlos Alberto; Corrêa, Ana Paula Simoes [UNESP]; Coleté, Juliana Zorzi [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Júnior, Idelmo Rangel Garcia [UNESP] (Wolters Kluwer, 2016)
Rhinocerebral zygomycosis is a rare condition characterized by infection initially in the nose and paranasal sinuses with atypical symptoms consistent with sinusitis. Once established in the nasal sinuses, the infection can easily spread to the orbital region and brain. In the localized form of the infection, the mortality rate is approximately 10%, which increases in the occurrence of orbital involvement and survival in patients of cerebral dissemination is extremely rare. The present paper reports a patient of nasal zygomycosis with orbital and cerebral dissemination in an otherwise healthy patient who survived after 14 months of hospitalization with no neurological impairment. A review of the literature addressing aspects related to diagnosis, treatment, and complications of this fungal infection is also presented.
Keywords: Cerebral abscess; Magnetic resonance imaging; Zygomycosis